Finding the New Radical: Digital Media, Oppositionality, and Political Intervention in Contemporary Canadian Theatre - McLeod, Kimberley (Theatre Research in Canada / Recherches théâtrales au Canada, 2014)
Alan Filewod argues that in contemporary performance, “Digital media is both the means and the form of the reconstitution of activist theatre: it disrupts and relocates cultural genealogies, reterritorializes artistic traditions, produces new structures. Digitalization is the enabling condition, then, of new theatricalities.” In November 2011, Quebec playwright Oliver Choinière created a digital performance that, in line with Filewod’s claim, challenged existing theatre conventions and explored new possibilities for activist performance interventions. His performance, Project blanc , used pre-recorded audio on MP3 players, which participants clandestinely listened to while watching a production of L’École des femmes at Montreal’s Théâtre du Nouveau Monde. The audio was critical of both the production and the theatre’s role as a commercial institution. This article investigates the relationship between this production’s oppositional stance and use of digital tools. Choinière’s protest performance creates affinity and proximity within his audience, thus working against what Jason Farman refers to as the “distancing-through-proximic” that usually occurs when individuals are connected to mobile devices in public. However, the production’s own exclusivity and antagonistic tone undermines Choinière’s critical stance. Another digital site-specific performance, Jonathan Goldsbie’s Route 501 Revisited, provides a counterpoint to Choinière’s approach. This example, which had participants ride on a Toronto streetcar and communicate through a Twitter hashtag, illustrates the potential for mobile technologies to politicize spaces and users via performance. While Goldsbie’s work is less overtly political in its aims, his encouragement of collaboration contrasts with Choinière’s more traditional narrative approach and oppositionality.